A strategy for the forest sector in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
A strategy for the forest sector in suh-Saharan Africa by N Sharma S Rietbergen, C Heimo and J Patel 1994